2014
DOI: 10.1080/00140139.2014.983184
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a slack-pulling device in reducing operator physiological workload during log winching operations

Abstract: The authors conducted a comparative test to determine whether the introduction of a hydraulic slack puller allowed reducing the physiological workload of operators assigned to log winching tasks. The tests were conducted in northern Italy, on the mountains near Como. The study involved five volunteer subjects, considered representatives of the regional logging workforce. Physiological workload was determined by measuring the operators' heart rate upon completion of specific tasks. The slack puller improved the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…The mental workload and the fatigue associated with various types of forestry tasks have already been studied using scientific methods, including: measurement of electrodynamic activity, determination of cardiovascular activity, electromyography, monitoring of respiratory frequency and amplitude, measurement of temperature, and electroencephalography (Stampfer 1998;Filo 2014;Spinelli et al 2015;Aalmo et al 2016;Tadeusiewicz et al 2017). Due to the high complexity and cost of the equipment required for objective measurements, subjective survey methods are also used to measure mental workload and fatigue, such as the Japanese Fatigue Feeling Scale and the NASA TLX method (Hart and Staveland 1988).…”
Section: Discussionmentioning
confidence: 99%
“…The mental workload and the fatigue associated with various types of forestry tasks have already been studied using scientific methods, including: measurement of electrodynamic activity, determination of cardiovascular activity, electromyography, monitoring of respiratory frequency and amplitude, measurement of temperature, and electroencephalography (Stampfer 1998;Filo 2014;Spinelli et al 2015;Aalmo et al 2016;Tadeusiewicz et al 2017). Due to the high complexity and cost of the equipment required for objective measurements, subjective survey methods are also used to measure mental workload and fatigue, such as the Japanese Fatigue Feeling Scale and the NASA TLX method (Hart and Staveland 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in motor-manual felling, estimates from the same flat-land area and for a worker having an age close to the average of this study [17] were close to those found in this study. In steep terrain forests of Turkey, for instance, harvesting and forest nursery work was found to be difficult to moderate jobs with heart rate reserves of approximately 41 and 32%, respectively [39], while jobs such as cable work in steep terrain [40,41] and cable rigging [42] may take more effort.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of heart rate reserve, however, the results of this study indicated smaller workloads compared to [72] where the terrain slope was high (50-80%) and the work tasks shares in the study time were not mentioned, and close to those reported by [55] for the effective chainsaw work and for different delays. In choker setting tasks, heart rate reserve accounts for 36.4% [52] under conditions of steep terrain, in cable work it ranges between 21.6 and 76%, depending on the tasks and tools used [19,54], and cable rigging operations seem to put heavier strains on the workers with a heart rate reserve in the range of 67-80% [53]. Exposure to noise of motor-manual tree felling and processing, as reported in this study, was greater than that specific to skidding [58] and chipping operations [46,59].…”
Section: Discussionmentioning
confidence: 99%
“…Heart rate reserve is a common indicator used in describing the difficulty of work, especially in those work environments in which the use of more accurate and sophisticated ergonomic instruments is difficult. Therefore, it was used in many forest operation-related studies [19,20,[52][53][54][55][56] and it represents a good estimator of the VO2 indicator in forest operations [57] that is commonly used to predict the work intensity in general ergonomic studies. %HRIi = (HRwi -HRr)/(HRr) × 100…”
Section: Data Processing and Analysismentioning
confidence: 99%